1982
DOI: 10.1111/j.1365-2125.1982.tb04934.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of chlormezanone and nitrazepam on sleep.

Abstract: 1 Twelve volunteers, of mean age 60 years, took part in a double-blind, balanced cross-over study, to compare effects of chlormezanone 400 mg and nitrazepam 5 mg on electrophysiologically-recorded and subjectively-rated sleep. 2 In the first week of administration nitrazepam caused a significant shortening of the time to fall asleep, but following withdrawal subjects took longer to fall asleep than during the baseline period. 3 Both chlormezanone and nitrazepam initially caused increase of sleep duration and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The increase of sleep duration and the reduction in the brokenness of sleep caused by promethazine parallel what is found in middle-aged poor sleepers after, for example, nitrazepam 5 mg or chlormezanone 400 mg (Adam & Oswald, 1982), lormetazepam 1 mg , loprazolam 1 mg or triazolam 0.5 mg , and it is of interest that since 1985 promethazine has been marketed in the United Kingdom as a non-prescription hypnotic. The Significance refers to within-subject comparisons and placebo-20 mg or placebo-40 mg differences present study was, however, limited to the effects of single dosages only, whereas in the other studies cited, assessment was made of any tolerance during 3 weeks of regular intake and of any later withdrawal effects.…”
Section: Discussionsupporting
confidence: 52%
“…The increase of sleep duration and the reduction in the brokenness of sleep caused by promethazine parallel what is found in middle-aged poor sleepers after, for example, nitrazepam 5 mg or chlormezanone 400 mg (Adam & Oswald, 1982), lormetazepam 1 mg , loprazolam 1 mg or triazolam 0.5 mg , and it is of interest that since 1985 promethazine has been marketed in the United Kingdom as a non-prescription hypnotic. The Significance refers to within-subject comparisons and placebo-20 mg or placebo-40 mg differences present study was, however, limited to the effects of single dosages only, whereas in the other studies cited, assessment was made of any tolerance during 3 weeks of regular intake and of any later withdrawal effects.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that over 20% of adults in Japan suffers from insomnia (8), and sleep is a serious social issue in Japan and other countries. Psychological disorders can greatly affect sleep quality and are regarded as a cause of insomnia (9,10). Because GABA can effectively relieve stress and anxiety, it is conceivable that GABA could improve sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…In general, antianxiety drugs are also effective for the improvement of sleep because psychological disorders such as stress, depression and anxiety are deeply involved in sleep quality (9,10). GABA is known to have effects of anti-stress and relaxation (3)(4)(5)(6), and AVLE is also effective for relieving depression (7) and anxiety (8).…”
Section: Discussionmentioning
confidence: 99%
“…2), shows antidepressant effects (7) and antianxiety and antihypertensive activities (8). Since both GABA and AVLE have effects on psychological disorders, which are deeply involved in sleep quality (9,10), the improvement of sleep can be expected from ingestion of them. In fact, GABA has been reported to help elderly people to sleep well (11), and AVLE has been recorded in 'Pharmacopoeia of People's Republic of China' and used as an herbal medicine to treat insomnia in China (12).…”
mentioning
confidence: 99%